Generation Y’s Expectation and Perception towards Hotels’ Quality of Services in Malaysia - Pang, Shin Yun; Ahmad, Rozila (2017)
Generation Ys has become the main target market in Malaysia replacing the Baby Boomers and the Generation X. The number of Generation Ys traveling around the world is increasing. However, Generation Ys are hard to predict, as they expect new experiences to be provided by the hotels. Therefore, from these factors, changes in terms of new initiatives are needed to seize this market. Improving quality of services will allow the organization to grow and survive in the competitive market.